Efektivitas Metode Bernyanyi Terhadap Kemampuan Berbahasa Anak Usia Dini Di Taman Kanak-Kanak Islam Shabrina Kota Padang - Ramadhani, Ayu; Marlina, Serli (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Language development is one of the essential indicators that reflects the cognitive, social, and emotional growth of early childhood. This ability is strongly influenced by the learning environment, particularly in early childhood education institutions. However, preliminary observations at Shabrina Islamic Kindergarten, Nanggalo District, Padang City, revealed that some children still experienced limited vocabulary and unclear pronunciation, while the teaching methods applied by teachers tended to be conventional and did not fully motivate children to actively use language. This study aimed to examine the effectiveness of the singing method in developing children’s language skills. The research employed a quantitative approach with a pretest–posttest design. The sample consisted of 10 children who participated in learning activities through the singing method. Data were collected using language ability tests administered before and after the treatment, and the results were analyzed using a t-test with Equality of Variances. The findings showed a significant difference between the pretest and posttest scores with a significance level (Sig) < 0.05. These results indicate that the singing method effectively enhances children’s language abilities. The study concludes that singing can serve as an alternative learning strategy that is enjoyable, interactive, and capable of stimulating vocabulary enrichment and pronunciation improvement in early childhood. The implication suggests that incorporating music-based learning methods into early childhood education curricula is crucial to support children’s optimal language development